High-strength steel with excellent fatigue resistance and corrosion resistance for lamp poles and method for manufacturing the same

CN122669304BActive Publication Date: 2026-10-20BENGANG STEEL PLATES CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611171079.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-04
Publication Date
2026-10-20
Estimated Expiration
2046-08-04

AI Technical Summary

Technical Problem

1、市场上输电铁塔用钢管杆的材质为Q235B、Q355B等钢板,产品强度偏低,致使钢管壁厚增加,钢材用量增加,成本提高

Benefits of technology

1、本发明钢种采用P-Cr-Cu协同效应,同时添加Ti、V,起到析出强化、细化晶粒以及沉淀强化效果,Cr、Ti和V在钢中形成金属间化合物,在大气环境、氯离子环境下,这些金属间化合物在钢板表面聚集,有效地阻止了腐蚀的发生。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122669304B_ABST
    Figure CN122669304B_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of steel metallurgy, and particularly relates to a high-strength steel for lamp poles with excellent fatigue resistance and corrosion resistance and a preparation method thereof. The chemical composition of the steel is as follows: C 0.047%-0.068%, Si 0.004%-0.027%, Mn 1.04%-1.24%, P 0.056%-0.068%, S≤0.005%, Ti 0.054%-0.073%, Cr 1.26%-1.44%, Cu 0.62%-0.76%, V 0.065%-0.085%, Alt 0.024%-0.046%, N 0.0022%-0.0034%, and the steel satisfies the conditions of Mn / C: 15-27, Ti / N: 15-34, and (Ca+Pr+La) / S: 10-14, and the balance is Fe. The steel has high strength and toughness, good fatigue resistance, corrosion resistance and cold bending forming performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of iron and steel metallurgy technology, and particularly relates to a high-strength steel for lamp posts with excellent fatigue resistance and corrosion resistance, and its preparation method. Background Technology

[0002] With the sustainable development of my country's national economy, urban electricity consumption has surged, leading to a proliferation of power transmission lines. Due to the numerous components, heavy weight, complex design, high processing and transportation costs, and long construction periods associated with angle steel towers, they are gradually being replaced by lightweight steel pipe poles—which are simpler in design, easier to process and transport—for 110kV, 220kV, and even 500kV transmission lines. Steel pipe poles occupy less space, have an aesthetically pleasing appearance, and blend well with the surrounding environment; while angle steel towers are difficult, if not impossible, to achieve small root openings and are less aesthetically pleasing.

[0003] Due to their low wind pressure, high rigidity, simple structure, reasonable stress distribution, and clear force transmission, steel pipe poles for power transmission lines can withstand greater loads. They also enhance the ability of power transmission lines to resist natural disasters under extreme conditions and improve the safety of power transmission line use. Therefore, steel pipe towers meet the needs of future large-capacity, long-distance, and high-voltage power transmission and communication base station construction, and have broad market prospects.

[0004] Currently, with the strengthening of urban infrastructure construction in my country, steel pipe poles for power transmission lines have the following shortcomings: 1. The steel pipe poles used for power transmission towers on the market are made of steel plates such as Q235B and Q355B, which have low strength. This leads to an increase in the wall thickness of the steel pipes, an increase in the amount of steel used, and an increase in cost.

[0005] 2. The existing materials have poor corrosion resistance and need to be replaced every 3 to 5 years.

[0006] 3. The existing materials have low strength, resulting in a low fatigue life.

[0007] 4. The existing material has a relatively thick wall, which increases the number of welding passes.

[0008] 5. The production efficiency and yield of existing steel pipe poles are relatively low.

[0009] In response to this situation, there is an urgent need to develop a high-strength steel for light poles. Summary of the Invention

[0010] To overcome the shortcomings of the prior art, the purpose of this invention is to provide a high-strength steel for light poles with excellent fatigue resistance and corrosion resistance, and a method for preparing the same steel. This method can reduce the wall thickness of the steel pipe while bearing the same load as the steel pipe pole, thus saving steel consumption. It can also reduce the number of welding passes, increase fatigue life, and improve yield and production efficiency.

[0011] To achieve the above objectives, the present invention provides the following technical solution: A high-strength steel for light poles with excellent fatigue resistance and corrosion resistance, wherein the chemical composition of the steel, by weight percentage, comprises: C: 0.047%~0.068%, Si: 0.004%~0.027%, Mn: 1.04%~1.24%, P: 0.056%~0.068%, S≤0.005%, Ti: 0.054%~0.073%, Cr: 1.26%~1.44%, Cu: 0.62%~0.76%, V: 0.065%~0.085%, Alt: 0.024%~0.046%, N: 0.0022%~0.0034%, with the balance being Fe and unavoidable impurities; and simultaneously satisfying Mn / C: 15~27; Ti / N: 15~34, (Ca+Pr+La) / S: 10~14; Ceq≤0.64; Pcm≤0.25; Wherein, Ceq = C + Mn / 6 + (Cr + V + Mo) / 5 + (Cu + Ni) / 15; Pcm=C+Si / 30+Mn / 20+Cu / 20+Cr / 20+Ni / 60+Mo / 15+V / 10+5B.

[0012] The microstructure of the steel is ferrite + bainite, with spherical Mn-SOP-Ca-Pr inclusions, as well as LaS, La2O3, and La2O2S inclusions distributed within the ferrite matrix. It also contains a large number of VC, TiC, and VN nano-precipitates with a size smaller than 5.5 nm. These inclusions and precipitates can act as stable internal and external rust layers, significantly improving the fatigue performance and corrosion resistance of the high-strength steel used in lamp posts.

[0013] The steel plates rolled from the steel have a size of 2.0~16.0mm × 1820~2020mm.

[0014] The steel plate has a yield strength of 770~800MPa, a tensile strength of 815~850MPa, and an elongation after fracture A. 50With a strength of 35-45%, an impact energy ≥200J at -80℃, and measured according to GB / T3075 "Metallic Materials Fatigue Test Axial Force Control Method" and GB / T24176 "Metallic Materials Fatigue Test Data Statistical Scheme and Analysis Method", this high-strength steel has a fatigue life of 1.84 million cycles, which is 800,000 cycles higher than Q355B. Its relative corrosion rate compared to Q355B is ≤35%, and it also meets the cold bending performance requirements of 180° and d=1.0a. The steel plate inclusion test results are as follows: Class A ≤0.5 grade, Class B ≤0.5 grade, Class C ≤0.5 grade, Class D ≤0.5 grade, Class DS ≤1.0 grade, and the total of all inclusions ≤2.0 grade. This indicates that the performance of this high-strength steel far exceeds that of existing light poles, and there is still room for further thinning. Therefore, using high-strength steel for light poles can achieve energy saving and consumption reduction, and it also has excellent fatigue performance and corrosion resistance.

[0015] The role of each chemical element in this invention is mainly based on the following principles: C: In lamp post steel, it exists in the form of TiC, interstitial solid solution, and cementite, and is the most important strengthening element in steel. It plays a beneficial role in improving the strength of lamp post steel, and nano-sized TiC is beneficial for fatigue resistance and crack arrest performance. Too high a C content is detrimental to the weldability and surface quality of lamp post steel, while too low a C content is detrimental to the strength of lamp post steel. Therefore, C is controlled at 0.047%~0.068%.

[0016] Si plays a role in calming and deoxidizing. It exists in austenite or ferrite in solid solution form. Si in steel has strong solid solution strengthening and cold working deformation capabilities, which shifts the C-curve to the right and improves the strength of steel. A certain amount of Si can promote carbon diffusion and reduce the carbon content in austenite, which is beneficial to the stability of (supercooled) austenite. Therefore, the Si content should be controlled between 0.004% and 0.027%.

[0017] Mn can improve the strength and hardenability of steel, reduce the bainite transformation temperature, and increase the overheating sensitivity of steel. Under slight overheating, the grains grow significantly. Therefore, the Mn content should be controlled at 1.04%~1.24%, while satisfying Mn / C=15~27.

[0018] Cr, Cu: Cr can form M2C3 and Mn2C3 in steel. 23Various carbides, such as C6 and M3C, can form continuous solid solutions with Fe, resulting in solid solution strengthening and a secondary strengthening effect. Cr promotes the formation of a dense passivation film or protective rust layer on the steel surface, and its enrichment within the rust layer effectively improves the selective permeability of the rust layer to corrosive media, thereby improving the passivation ability of the steel. Simultaneously, Cr can increase the self-corrosion potential of the steel, improving its resistance to atmospheric corrosion. Chromium and copper are preferably added to form a dense and uniform internal and external corrosion layer on the lamp post surface. Since expensive nickel is not added, the Cr content is limited to 1.26%~1.44%, and the Cu content is limited to 0.62%~0.76%.

[0019] V: It plays a precipitation strengthening role in steel, existing in the form of VC, VN and V (C, N), which is beneficial to improving the strength of steel. The optimal addition amount of V is 0.065%~0.085%.

[0020] P promotes the formation of a protective rust layer on the surface, improves the corrosion resistance of steel, and increases its strength. However, P tends to agglomerate at the boundaries, reducing the ductility, toughness, and grain boundary bonding energy of steel. Therefore, P is limited to 0.056%~0.068%.

[0021] Nitrogen (N) forms AlN and TiN in steel. These fine precipitates help to pin grain boundaries and refine austenite grains. AlN nonmetallic inclusions disrupt the continuity of the steel matrix, and higher N concentrations tend to accumulate at defects, worsening low-temperature impact toughness. Therefore, the N content is limited to 0.0022%~0.0034%.

[0022] Ti exists in steel in the forms of TiC, TiN, and Ti(C, N). It is a carbonitride and strong ferrite-forming element, readily forming complexes with O, S, C, and N. TiN in steel can also inhibit austenite grain growth, playing a role in precipitation strengthening and refining the microstructure. Furthermore, Ti can prevent the recrystallization of deformed austenite and promote the formation of granular bainite. The precipitated Ti(C, N) particles can suppress grain coarsening in the weld heat-affected zone, further improving weldability. Therefore, a Ti content of 0.054%~0.073% is specified, while simultaneously satisfying a Ti / N ratio of 15~34.

[0023] Ca, Pr, and La: Their main function is to modify inclusions, acting as oxide metallurgy to form spherical and dot-like Mn-SOP-Ca-Pr inclusions, as well as LaS, La2O3, and La2O2S inclusions. These inclusions hydrolyze in the thin corrosion film and precipitate at the cathode with a higher pH value, thus playing a role in corrosion inhibition and improving the fatigue performance and corrosion resistance of the steel used for lamp posts. Therefore, it is specified that (Ca+Pr+La) / S=10~14.

[0024] A method for preparing high-strength steel for lamp posts with excellent fatigue resistance and corrosion resistance includes: hot metal pretreatment → smelting → continuous casting → heating → hot rolling → laminar flow cooling → coiling → slow cooling. Heating: The heating temperature of the continuously cast billet is 1162~1182℃, and the heating time is 114~124min; Hot rolling: divided into roughing and finishing rolling. R1 and R2 of roughing adopt the "0+7" mode. The initial rolling temperature of roughing is 1115~1135℃. The reduction of the first two passes of roughing is 35mm and 35mm respectively. The reduction of the last pass is 20mm. The remaining reduction is distributed to other passes. The thickness of the intermediate billet is 46~60mm. The initial rolling temperature of the finishing mill is 934~938℃. The last pass of the roughing mill is used as the first pass of the finishing mill. The finishing mill F5 is abandoned, and the final rolling temperature is 795~805℃. Laminar flow cooling: The front-end cooling mode is adopted. Water cooling is applied immediately after F7 is produced. The cooling rate is 21~25℃ / s, the cooling water temperature is ≤25℃, and side spray water is introduced. The side spray water pressure is 1.0~1.2MPa. The purpose is to eliminate water accumulation on the surface of the strip, reduce uneven cooling of the steel plate, and improve control accuracy. Winding: A three-roller hydraulic step winder is used for winding, and the maximum power of the winder is 1400kW; Slow cooling: The coiled steel plate is placed in a slow cooling pit for slow cooling treatment, and can only be moved after 24~36 hours.

[0025] The hot metal pretreatment adopts desulfurization by powder injection, in which a mixture of magnesium powder and lime powder is injected into the torpedo car at a ratio of 1:(4.0~5.0) to make the sulfur content of the hot metal entering the converter ≤0.005%.

[0026] The smelting process involves using scrap steel and molten iron as raw materials, which are added to the converter in a ratio of (30~40):(150~140). A top-and-bottom combined blowing converter is used for smelting. Nitrogen is blown into the bottom during the early stage of smelting, and argon is switched during the tapping process. The tapping temperature is ≥1685℃, the tapping time is 4~7min, and the tapping port is round. The refining process employs a dual-station approach: firstly, LF ladle furnace refining is performed, with aluminum used for precipitation deoxidation in the early stages of refining, and aluminum and calcium carbide added for diffusion deoxidation during the refining process; then, vacuum RH circulation treatment is carried out to remove C and H from the steel, and soft argon blowing is performed at the end of refining, with an argon blowing time of ≥16min, and Mn, Cr, Cu, and V are added for alloying, and Ca, Pr, and La are added for inclusion modification treatment.

[0027] The continuous casting process employs a continuous casting machine with a chamfered crystallizer to reduce corner cracks and lower the rate of downgraded products. Constant casting speed is used, controlled at 1.20~1.30 m / min. The protective slag is a special XX-3D slag system for corrosion-resistant steel. The superheat is controlled at 12~18℃ (by using a special corrosion-resistant steel protective slag and controlling the casting speed and superheat, the secondary dendrite spacing in the solidified structure of the continuously cast billet can be reduced, which helps improve center segregation, center porosity, shrinkage cavities, and internal cracks, and effectively controls the internal structure). The secondary cooling system of the slab continuous casting machine adopts a weak cooling mode, and electromagnetic stirring is used in the fan-shaped section of the secondary cooling zone to maintain the temperature of the molten steel and the solidified billet. The shell is uniform with an equiaxed crystal ratio of ≥93%, improving surface quality. Simultaneously, mechanical reduction is applied to two fan-shaped sections after electromagnetic stirring in the secondary cooling zone at the end of the slab continuous casting solidification, controlling the cumulative reduction to 13~15mm to obtain a homogeneous slab (by optimizing the battery stirring process in the continuous casting stage, the columnar crystal ratio is significantly reduced, and the equiaxed crystal ratio of the continuous casting slab is increased. At the same time, light reduction is applied, which helps to reduce slab segregation, reduce internal structural defects, and elongate and break up the core grains, thus ensuring the improvement of the material's strength and toughness). The continuously cast slabs are cut into fixed lengths and hot-fed into the heating furnace, effectively promoting the full dissolution of microalloying elements such as Cr, V, Ti, Mn, and Ti, reducing the impact of their compositional separation and crystallization on material properties and microstructure.

[0028] This invention employs a P-Cr-Cu composition system, achieving a significant improvement in corrosion resistance under atmospheric and high-chloride soil corrosion environments through the synergistic effect of multiple corrosion-resistant elements. The key lies in utilizing the synergistic effect of P, Cr, and Cu. P is typically used in high-strength steel to improve corrosion resistance and hardenability, or Cr and Cu are used to suppress critical brittleness and pitting corrosion caused by high P content, thereby improving the corrosion resistance of steel plates in seawater. This invention's research found that under atmospheric corrosion and chloride ion environments, P combined with Cr and Cu, at a concentration not exceeding 0.10%, can significantly improve the corrosion resistance of steel. Analysis suggests that this unique synergistic effect may be related to the fact that P, Cr, and Cu are in adjacent groups in the periodic table, thus possessing similar chemical properties and facilitating their combination. The synergistic effect of these three elements increases the self-corrosion potential and charge transfer resistance of the steel under these corrosive environments, reduces its corrosion current density, and the enrichment of P within the rust layer effectively hinders further corrosion of the matrix, thereby significantly improving its corrosion resistance.

[0029] This invention refines the original austenite microstructure of the steel plate by using a lower rolling temperature in the austenite recrystallization zone and a larger roughing deformation, thereby improving the fatigue resistance of the steel plate. Furthermore, a higher reduction rate in the final roughing pass further refines the core microstructure, reducing center segregation and porosity. In addition, by controlling the initial rolling temperature, final rolling temperature, cooling rate, and final cooling temperature of the finishing roll, the pearlite transformation zone is avoided using a relatively high cooling rate and a lower final rolling temperature, suppressing the formation of pearlite microstructure. Simultaneously, the higher cooling rate increases the phase transformation rate of the steel plate, inhibiting element diffusion and segregation, reducing banded microstructure, and improving fatigue and corrosion resistance. The resulting steel plate exhibits a acicular ferrite microstructure, achieving a good balance between toughness, strength, crack arrest performance, and fatigue performance.

[0030] Furthermore, the high-strength steel of this invention also contains 0.054~0.073% Ti and 0.065~0.085% V, which exist in the steel as Ti(C, N) and V(C, N), playing a role in precipitation strengthening, grain refinement, and sedimentation strengthening. Under natural conditions, it has a passivation effect, forming a thin film on the surface of the steel plate, thereby slowing down corrosion. According to the research of this invention, Cr, Ti, and V form intermetallic compounds in the steel. In atmospheric and chloride ion environments, these intermetallic compounds accumulate on the surface of the steel plate, effectively preventing corrosion.

[0031] The high-strength steel of the present invention also contains Ca, Pr, and La, forming spherical and dot-like Mn-SOP-Ca-Pr inclusions, as well as LaS, La2O3, and La2O2S inclusions. These inclusions hydrolyze in the thin corrosion film and precipitate at the cathode with a high pH value, thereby playing a role in corrosion inhibition and improving fatigue performance and corrosion resistance.

[0032] In this invention, P and Cr are used to increase the matrix potential. Cr combines with P and Cu in the steel in a certain ratio, which is beneficial to ensure good corrosion resistance in atmospheric corrosion environment and chloride ion environment. Among them, P plays a precipitation strengthening role, while Cr and Cu have solid solution strengthening effect. While improving the strength of the steel plate, it can also improve the corrosion resistance.

[0033] In this invention, Ceq ≤ 0.64 and Pcm ≤ 0.25 are specified. Carbon equivalent and cold crack sensitivity coefficient are core indicators for measuring the influence of steel's chemical composition on the hardening tendency and cold crack sensitivity of the weld heat-affected zone. Higher values ​​indicate a higher total content of carbon and alloying elements in the steel, leading to a greater likelihood of forming a hard and brittle microstructure during rapid cooling after welding. This microstructure transformation directly results in a sharp increase in hardness and a significant decrease in plasticity and toughness in the weld heat-affected zone, thereby greatly increasing the risk of cold cracking. Extensive testing has shown that by limiting Ceq to ≤ 0.64 and Pcm to ≤ 0.25, good weldability of the steel can be guaranteed, effectively suppressing crack formation and ensuring the safety of the welded joint.

[0034] By combining the aforementioned elements, the steel plate achieves comprehensive performance characteristics of high strength, toughness, and resistance to various corrosive media. This results in a relative corrosion rate (compared to Q355B) ≤35% in atmospheric environments and fatigue performance (compared to Q355B) increased by over 800,000 cycles, meeting corrosion resistance requirements in diverse environments. This significantly improves corrosion resistance and makes it an environmentally friendly product. The high-strength steel of this invention features high strength, good toughness, low silicon content, and excellent galvanizing effect.

[0035] This invention fully utilizes the phase transformation strengthening and solid solution strengthening effects of Ti and V, as well as the precipitation strengthening and sedimentation strengthening effects of Cr, Cu, and P, to achieve a yield strength ≥750MPa, tensile strength ≥800MPa, good low-temperature impact toughness (impact energy ≥200J at -80℃), and elongation at break (A50) ≥32%. It also exhibits excellent cold bending performance, meeting the requirements for 180° cold bending with d=1.0a. This invention combines high strength and toughness with high corrosion resistance, and also possesses good formability and weldability, meeting the requirements for steel used in lamp posts.

[0036] Compared with the prior art, the beneficial effects of the present invention are: 1. The steel grade of this invention adopts the P-Cr-Cu synergistic effect, and at the same time adds Ti and V to achieve precipitation strengthening, grain refinement and precipitation strengthening effects. Cr, Ti and V form intermetallic compounds in the steel. In atmospheric environment and chloride ion environment, these intermetallic compounds accumulate on the surface of the steel plate, effectively preventing corrosion.

[0037] 2. This invention adds Ca, Pr, and La to form spherical and dot-like Mn-SOP-Ca-Pr inclusions, as well as LaS, La2O3, and La2O2S inclusions. These inclusions hydrolyze in the thin corrosion film and precipitate at the cathode with a high pH value, thereby playing a role in corrosion inhibition and improving fatigue performance and corrosion resistance.

[0038] 3. The steel grade of this invention possesses excellent mechanical properties, with a yield strength ≥750MPa and a tensile strength ≥800MPa. It also exhibits good low-temperature impact toughness, with an impact energy ≥200J at -80℃ and an elongation after fracture (A) 50 It has a strength of ≥32%, and excellent cold bending performance, meeting the cold bending requirements of 180° and d=1.0a.

[0039] 4. The steel grade of this invention is produced using controlled rolling and controlled cooling. Throughout the entire cooling rate range, the phase transformation mainly occurs between 470℃ and 750℃, resulting in low deformation resistance and reduced energy consumption and equipment load. Controlling the coiling temperature to 450~465℃ generates a greater amount of bainite, improving the strength of the steel plate. Delivered in the hot-rolled state, this steel grade requires a post-rolling cooling rate of at least 20℃ / s, reducing the difficulty of cooling control, providing a wider process control window, and eliminating the need for heat treatment. The production process is simple, the rolling cycle is short, and it can be implemented using existing rolling mill equipment.

[0040] 5. In addition to having good corrosion resistance and high strength and toughness, this invention also has good cold bending, welding and other forming properties, making it particularly suitable for various cold forming processes in the production of steel for urban infrastructure construction and iron transportation; it can also be applied to atmospheric corrosion environments, chloride ion corrosion environments such as seawater, and steel pipe pole construction. Attached Figure Description

[0041] Figure 1 This is the CCT curve diagram of the present invention.

[0042] Figure 2 This is a microstructure diagram of Example 1.

[0043] Figure 3 This is the inclusion inspection (B0.5D0.5) diagram of Example 1. Detailed Implementation

[0044] The present invention will now be described in detail with reference to the accompanying drawings, but it should be noted that the implementation of the present invention is not limited to the following embodiments.

[0045] A high-strength steel for light poles with excellent fatigue resistance and corrosion resistance, the chemical composition of which, by weight percentage, includes: C: 0.047%~0.068%, Si: 0.004%~0.027%, Mn: 1.04%~1.24%, P: 0.056%~0.068%, S≤0.005%, Ti: 0.054%~0.073%, Cr: 1.26%~1.44%, Cu: 0.62%~0.76%, V: 0.065%~0.085%, Alt: 0.024%~0.046%, N: 0.0022%~0.0034%, and satisfying Mn / C: 15~27, Ti / N: 15~34, (Ca+Pr+La) / S: 10~14; Ceq≤0.64; Pcm≤0.25; balance Fe and unavoidable impurities; Wherein, Ceq = C+Mn / 6+(Cr+V+Mo) / 5+(Cu+Ni) / 15; Pcm=C+Si / 30+Mn / 20+Cu / 20+Cr / 20+Ni / 60+Mo / 15+V / 10+5B.

[0046] The chemical composition of the steels used in the examples is shown in Table 1, the production process parameters are shown in Table 2, and the properties are shown in Table 3. Figures 1-3 The microstructure of the steel in Example 1 is 78% ferrite + 22% bainite.

[0047] This invention employs a controlled rolling and cooling process in hot continuous rolling. The lower rolling temperature in the austenite recrystallization zone and the larger roughing deformation allow for thorough refinement of the original austenite microstructure in the steel plate. Finishing rolling is controlled within the entire austenite region. A higher cooling rate increases the phase transformation rate of the steel plate. During post-rolling layer cooling, the cooling rate is controlled to be above 20℃ / s. This provides a wide process window, reduces production difficulty, and facilitates on-site control. The resulting steel plate exhibits a acicular ferrite microstructure. The steel grade of this invention exhibits excellent corrosion resistance in soil environments with sulfate ion concentrations of 500–50000 mg / kg and chloride ion concentrations of 2000–10000 mg / kg, as well as in industrial atmospheric environments.

[0048] Table 1 Chemical composition of high-strength steel:

[0049] Continued from Table 1:

[0050] Table 2. Production process parameters for high-strength steel:

[0051] Table 3. Properties of high-strength steel:

[0052] In summary, the weathering steel described in this invention, in addition to possessing high strength and toughness, exhibits a corrosion rate of less than 15% compared to low-alloy steel Q355B in soil environments with sulfate ion concentrations of 500–50000 mg / kg and chloride ion concentrations of 2000–10000 mg / kg. Furthermore, its atmospheric corrosion resistance is less than 35% compared to low-alloy steel Q355B. This makes it particularly suitable for applications such as photovoltaic support steel, steel pipe poles for transmission towers, and steel for urban infrastructure construction, particularly in equipment subjected to chloride and sulfate ion corrosion, and in complex environments requiring resistance to industrial atmospheric corrosion and seawater corrosion.

[0053] The above embodiments are only for illustrating the technical concept and features of the present invention and are not intended to limit the present invention. Any equivalent substitutions or modifications made without departing from the essence of the present invention fall within the protection scope of the present invention.

Claims

1. A high-strength steel for light poles with excellent fatigue resistance and corrosion resistance, wherein the chemical composition of the steel, by weight percentage, comprises: C: 0.047%~0.068%, Si: 0.004%~0.027%, Mn: 1.04%~1.24%, P: 0.056%~0.068%, S≤0.005%, Ti: 0.054%~0.073%, Cr: 1.26%~1.44%, Cu: 0.62%~0.76%, V: 0.065%~0.085%, Alt: 0.024%~0.046%, N: 0.0022%~0.0034%, and satisfying Mn / C: 15~27, Ti / N: 15~34, (Ca+Pr+La) / S: 10~14; Ceq≤0.64; Pcm≤0.25; balance Fe and unavoidable impurities; Wherein, Ceq = C+Mn / 6+(Cr+V+Mo) / 5+(Cu+Ni) / 15; Pcm=C+Si / 30+Mn / 20+Cu / 20+Cr / 20+Ni / 60+Mo / 15+V / 10+5B; The method for preparing high-strength steel for lamp posts with excellent fatigue resistance and corrosion resistance includes: hot metal pretreatment → smelting → continuous casting → heating → hot rolling → laminar flow cooling → coiling → slow cooling. Heating: The heating temperature of the continuously cast billet is 1162~1182℃, and the heating time is 114~124min; Hot rolling: divided into roughing and finishing rolling. R1 and R2 of roughing adopt the "0+7" mode. The initial rolling temperature of roughing is 1115~1135℃. The reduction of the first two passes of roughing is 35mm and 35mm respectively. The reduction of the last pass is 20mm. The remaining reduction is distributed to other passes. The thickness of the intermediate billet is 46~60mm. The initial rolling temperature of the finishing mill is 934~938℃. The last pass of the roughing mill is used as the first pass of the finishing mill. The finishing mill F5 is abandoned, and the final rolling temperature is 795~805℃. Laminar flow cooling: The front-end cooling mode is adopted. Water cooling is applied immediately after F7 is produced. The cooling rate is 21~25℃ / s, the cooling water temperature is ≤25℃, and side spray water is introduced. The side spray water pressure is 1.0~1.2MPa. The purpose is to eliminate water accumulation on the surface of the strip, reduce uneven cooling of the steel plate, and improve control accuracy. Winding: A three-roller hydraulic step winder is used for winding, and the maximum power of the winder is 1400kW; Slow cooling: The coiled steel plate is placed in a slow cooling pit for slow cooling treatment, and can only be moved after 24~36 hours.

2. The high-strength steel for lamp posts with excellent fatigue resistance and corrosion resistance according to claim 1, characterized in that, The microstructure of the steel is ferrite + bainite, with spherical Mn-SOP-Ca-Pr inclusions, as well as LaS, La2O3, and La2O2S inclusions distributed in the ferrite matrix. At the same time, there are also a large number of VC, TiC, and VN nanoprecipitates with a size of less than 5.5 nm.

3. The high-strength steel for lamp posts with excellent fatigue resistance and corrosion resistance according to claim 1, characterized in that, The steel plates rolled from the steel have a size of 2.0~16.0mm × 1820~2020mm.

4. The high-strength steel for lamp posts with excellent fatigue resistance and corrosion resistance according to claim 3, characterized in that, The steel plate has a yield strength of 770~800MPa, a tensile strength of 815~850MPa, and an elongation after fracture A. 50 With a strength of 35-45%, an impact energy of ≥200J at -80℃, and measured according to GB / T 3075 "Method for Controlling Axial Force in Fatigue Tests of Metallic Materials" and GB / T 24176 "Statistical Scheme and Analysis Method for Fatigue Test Data of Metallic Materials", the fatigue life of this high-strength steel is 1.84 million cycles, which is 800,000 cycles higher than that of Q355B. The relative corrosion rate compared to Q355B is ≤35%, and it also meets the cold bending performance requirements of 180° and d=1.0a. The steel plate inclusion test results are as follows: Class A ≤0.5 grade, Class B ≤0.5 grade, Class C ≤0.5 grade, Class D ≤0.5 grade, Class DS ≤1.0 grade, and the total of all types of inclusions ≤2.0 grade.

5. A method for preparing high-strength steel for lamp posts with excellent fatigue resistance and corrosion resistance as described in any one of claims 1-4, comprising: hot metal pretreatment → smelting → continuous casting → heating → hot rolling → laminar flow cooling → coiling → slow cooling, characterized in that: Heating: The heating temperature of the continuously cast billet is 1162~1182℃, and the heating time is 114~124min; Hot rolling: divided into roughing and finishing rolling. R1 and R2 of roughing adopt the "0+7" mode. The initial rolling temperature of roughing is 1115~1135℃. The reduction of the first two passes of roughing is 35mm and 35mm respectively. The reduction of the last pass is 20mm. The remaining reduction is distributed to other passes. The thickness of the intermediate billet is 46~60mm. The initial rolling temperature of the finishing mill is 934~938℃. The last pass of the roughing mill is used as the first pass of the finishing mill. The finishing mill F5 is abandoned, and the final rolling temperature is 795~805℃. Laminar flow cooling: The front-end cooling mode is adopted. Water cooling is applied immediately after F7 is produced. The cooling rate is 21~25℃ / s, the cooling water temperature is ≤25℃, and side spray water is introduced. The side spray water pressure is 1.0~1.2MPa. The purpose is to eliminate water accumulation on the surface of the strip, reduce uneven cooling of the steel plate, and improve control accuracy. Winding: A three-roller hydraulic step winder is used for winding, and the maximum power of the winder is 1400kW; Slow cooling: The coiled steel plate is placed in a slow cooling pit for slow cooling treatment, and can only be moved after 24~36 hours.

6. The method for preparing a high-strength steel for lamp posts with excellent fatigue resistance and corrosion resistance according to claim 5, characterized in that, The hot metal pretreatment adopts desulfurization by powder injection, in which a mixture of magnesium powder and lime powder is injected into the torpedo car at a ratio of 1:(4.0~5.0) to make the sulfur content of the hot metal entering the converter ≤0.005%.

7. The method for preparing a high-strength steel for lamp posts with excellent fatigue resistance and corrosion resistance according to claim 5, characterized in that, The smelting process involves using scrap steel and molten iron as raw materials, which are added to the converter in a ratio of (30~40):(150~140). A top-and-bottom combined blowing converter is used for smelting. Nitrogen is blown into the bottom during the early stage of smelting, and argon is switched during the tapping process. The tapping temperature is ≥1685℃, the tapping time is 4~7min, and the tapping port is round. The refining process employs a dual-station approach: firstly, LF ladle furnace refining is performed, with aluminum used for precipitation deoxidation in the early stages of refining, and aluminum and calcium carbide added for diffusion deoxidation during the refining process; then, vacuum RH circulation treatment is carried out to remove C and H from the steel, and soft argon blowing is performed at the end of refining, with an argon blowing time of ≥16min, and Mn, Cr, Cu, and V are added for alloying, and Ca, Pr, and La are added for inclusion modification treatment.

8. The method for preparing a high-strength steel for lamp posts with excellent fatigue resistance and corrosion resistance according to claim 5, characterized in that, The continuous casting process involves using a continuous casting machine equipped with a chamfered crystallizer. The continuous casting employs a constant casting speed, controlled at 1.20~1.30 m / min. The protective slag uses the XX-3D slag system for corrosion-resistant steel, and the superheat is controlled at 12~18℃. The secondary cooling system of the slab continuous casting machine adopts a weak cooling mode. Electromagnetic stirring is used in the fan-shaped section of the secondary cooling zone, with an equiaxed crystal ratio ≥93%. Simultaneously, mechanical reduction is applied to the three fan-shaped sections after electromagnetic stirring in the secondary cooling zone at the end of the slab continuous casting solidification, controlling the total reduction to 13~15 mm. The slabs are then cut into fixed-length continuous casting billets and hot-sent to the heating furnace.

Citation Information

Patent Citations

  • High-strength steel sheet exhibiting superior stretch-flange formability and bendability, and method of preparing ingot steel

    CN103080358A

  • Steel for household appliance plate with limit width and thickness and high surface quality and preparation method of steel

    CN122189515A